Islamic Banking : Issues in Prudential Regulations and Supervision - Errico, Luca (IMF Working Papers; Working Paper, 1998)
This paper analyzes the implications of Islamic precepts on banks' structure and activities, focusing on banking supervision issues. It points out and discusses these issues in the context of a paradigm version of Islamic banking, as well as in frameworks that fall between the paradigm version and conventional banking. The case of Islamic banks operating in a conventional system is also examined.